COVID-19 Conspiracy Beliefs and Vaccination Intentions among Social Media Users - Gemenis, Kostas (My University, 2022)
More than a year after the introduction of vaccines against COVID-19, inoculation remains inconsistent and variable across countries. In this paper, we introduce a multi-item scale of COVID-19 related misinformation, skepticism, and conspiracy theories and investigate the effects of these beliefs on vaccine hesitancy. We report findings from a survey in Greece where participants were recruited via paid advertising on Facebook and the study sample was adjusted for demographic variables using a nationally representative reference sample. We show that the endorsement of COVID-19 conspiracy beliefs is the primary factor driving vaccine hesitancy, far exceeding the effect of all other demographic and attitudinal variables, including health status. Furthermore, a pre-registered randomized survey experiment showed that the effect cannot be attributed to respondents' exposure to the COVID-19 conspiracy theory questions of the survey. The paper concludes by discussing potential public policy implications for combating misinformation and promoting health literacy among social media users.
Keywords: health literacy; conspiracy theories; vaccine hesitancy; COVID-19; social media; vaccintion